Expansion of Women's Political Participation through Social Movements: The Case of the Red and Yellow Shirts in Thailand. (February 2018) - Buranajaroenkij, Duanghathai; Doneys, Philippe; Kusakabe, Kyoko; Doane, Donna L
This study examines the political implications of women's participation in social movements in Thailand. Based on interviews at protest sites and focus group discussions with movement participants as well as interviews with leaders and key informants, the study suggests that political socialization within what is commonly called the color-coded movements has resulted in women acquiring political knowledge and learning about political engagement while being increasingly accepted as competent political actors. Consequently, women have utilized the Red and Yellow Shirt movements to increase their engagement in politics in three different ways. First, women form groups to enhance their political roles and opportunities within the movements. Second, women are expanding their political roles beyond those offered by the color-coded movements by becoming informal representatives, bridging their communities with formal political agents and institutions. Finally, women are increasingly entering into formal politics through the support of their movements.